PERLINDUNGAN HUKUM TERHADAP ANAK NAKAL BERDASARKAN UU NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Lubis, Muhammad Ansori (Pascasarjana UDA, 2019)
Law Number 11 of 2012 concerning the Criminal Justice System for Children related to Law Number 3 of 1997 concerning Juvenile Courts brings a new paradigm in the handling of children facing the law, especially in this case children who commit crimes.The research method used in this study is a normative juridical research method; the study of legal principles, legal norms in the laws and regulations and court decisions.The research finding shows that legal protection of children in conflict with the law in the juvenile justice system is a special treatment in order to ensure the physical and mental growth of children as the next generation that must be considered in the future.So the goal of juvenile justice is not only to declare whether a concrete event is proven and then to make a verdict, but to settle a child's case, if it reaches the court level, the case must be resolved, not until the verdict cannot be implemented or even cause new cases or problems.